THE IMPORTANCE OF VOCABULARY INSTRUCTION IN DEVELOPING READING COMPREHENSION SKILLS AND EXPLORE EFFECTIVE STRATEGIES FOR TEACHING VOCABULARY IN CONTEXT. - Madaminova Muzifa Shukurullo qizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article explores the pivotal role of vocabulary instruction in nurturing reading comprehension skills and offers insights into effective strategies for teaching vocabulary within meaningful contexts. Research underscores the indispensable link between vocabulary knowledge and reading comprehension, emphasizing the significance of intentional vocabulary instruction in fostering students' ability to comprehend and engage with diverse texts. Through contextual learning, word analysis techniques, semantic mapping, and interactive activities, educators can create enriching experiences that empower students to acquire, understand, and apply new vocabulary effectively. By prioritizing vocabulary instruction within literacy curricula and employing research-based strategies, educators can equip students with the essential tools for unlocking the complexities of written texts and fostering lifelong literacy proficiency.